Um sistema de biotelemetria multifuncional para sinais ECG, EEG e EMG - Martins, Joaquim Francisco (2005)
This work describes the development of a multifunctional biotelemetry system capable of detecting and processing ECG, EEG and EMG signals in real time. The main hardware was designed to capture any one of those signals from the same input channel. The user can program the hardware for the desired signal and adjust its gain as necessary. The various features of the system are controlled by a dedicated micro-controller which is also responsible for sending the digital data to a RF transmitter. In order to reduce signal corruption, the data is encrypted in Manchester code prior to transmission. The main soﬂware runs on a standard IBM-PC microcomputer and is responsible for collecting data from the USB port, graphics and ﬁle manipulation. The software was designed to detect the type of signal been transmitted and adjust its gain accordingly. Also, the received data can be processed in the time domain or in the frequency domain. The final prototype is light, fairly small and easy to use. A number of experiments have shown that, even when there are physical barriers between the transmitter and the receiver modules, the transmitted signal shows excellent stability and minimum error.